Environmental Impact from River Damming for Hydroelectric Power Generation and Means of Mitigation (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
Nepal is rich with inland water resources and has great potential for electricity power generation. Hydropower is one of the most sustainable national income sources to increase the nation’s GNP. Relatively few water resources are under utilization, however, although some lakes in Pokhara valley and the Kulekhani storage type hydropower reservoir are successful in supporting multipurpose usage, combining electric power generation, irrigation and aquaculture. The Kaligandaki hydropower system is run of river, thus not feasible for cage fisheries; instead, it produces fingerlings of indigenous riverine fish for release into the river. The impoundments after damming the rivers adversely impact both fish biodiversity and local fishing communities. Ecosystem change destroys feeding as well as breeding grounds, with a resultant loss of fish species. Where the movement of migratory fish up and down river is affected by hydropower development, fish hatcheries near the dam sites or fish ladders for fish movement should be considered as mitigation options. Local user groups and other stakeholders should be involved in decision-making, to keep good relations concerning peoples’ livelihoods and the sustainability of aquatic resources. River systems should be thoroughly studied jointly with concerned agencies (e.g., electricity, irrigation and fisheries authorities; and local authorities) during formulation and application stages of hydroelectric power development projects. Hydro Nepal: Journal of Water, Energy and Environment Vol. 1, No. 2(2008) pp. 22-25